Quantificação de oocistos e ovos de parasitos gastrintestinais de cães por métodos de sedimentação e flutuação - Menezes, Eylha Pricilla Fernandes (Universidade Federal Rural do Semi-Árido, 2019)
The companion animals are considered definitive hosts or intermediates of several parasites and have high zoonotic potential, being responsible for the transmission of several zoonoses to the human being. The performance of parasitological diagnosis in samples of faeces from dogs can function as a good indicator of the level of gastrointestinal infection in these hosts and has assisted in the implementation of appropriate treatment measures as well as management aimed at the control or elimination of parasites. Among the existing techniques, there are those that allow the observation and quantification of protozoan oocysts and helminth eggs, such as direct analyzes, Hoffman sedimentation, Willis Mollay flotation and Mini-FLOTAC. Considering that dogs present high mortality in Mossoró, Rio Grande do Norte, in detriment of parasitism, the present work aimed to verify four techniques to quantify the elimination of eggs and oocysts of endoparasites in naturally infected dogs. For the analysis, stool specimens were obtained from 40 dogs, regardless of race, sex and age, with the premise that the animal had no vermifugation for at least 3 months. The faeces were obtained from the animals through spontaneous elimination and were individually conditioned and transported to the Laboratory of Animal Parasitology of the Federal Rural do Semi-Árido University (LPA-UFERSA) for later diagnosis. Each of the samples collected underwent direct analysis, Willis-Mollay flotation, Mini-FLOTAC and sedimentation. Oocysts and eggs were identified through morphology and with the aid of specific taxonomic keys. The data obtained from the coproparasitological analyzes were expressed in values of mean and standard deviation using the statistical program SPSS version 21.0. After analyzing the parametric assumptions, statistical differences between techniques were obtained by Friedman and Kruskal-Wallis. The agreement between the techniques was evaluated through the Kappa value. Values of p <0.05 were considered significant. From the analyzes performed on the 40 animals, positivity was detected for Ancylostoma spp., Dipylidium caninum, Toxocara spp., and Cystoisospora canis oocysts. The Mini-FLOTAC technique obtained higher potential for recovery of eggs of Ancylostoma spp. and D. caninum compared to the other techniques tested. For Cystoisospora canis and Toxocara spp., the techniques tested were the same. The direct examination and sedimentation techniques showed equal capacity to recover Ancylostoma spp. and D. caninum. For the techniques tested, the Mini-FLOTAC showed a greater efficiency of egg and oocyst recovery, followed by Willis Mollay, which, although smaller, had the same potential to detect eggs and oocysts positivity. The use of more than one technique for parasitological diagnosis is recommended, since a single method may not reveal true parasitism, especially considering that, in many cases, animals have multiple parasitism.
Monografia
Keywords: Exames coproparasitológicos; Mossoró-RN; Zoonose; Coproparasitological examinations; Mossoró-RN; Zoonosis; CIENCIAS AGRARIAS::MEDICINA VETERINARIA